Emergence of Meningitis Caused by Nonvaccine Serotypes of Pneumococcus in Rural United States - Jessie Marks; Guru V. Bhoojhawon; Katherine D. Patrick; Kelly E. Wood (Case Reports in Pediatrics)
Pneumococcal conjugate vaccines have decreased the rates of invasive pneumococcal disease (IPD) in children. Since vaccine introduction, however, rates of infection due to nonvaccine Streptococcus pneumoniae serotypes have increased. We now describe 3 meningitis cases due to the nonvaccine serotypes 35B and 11A from rural United States.